Community Service Provisions as an Alternative Punishment in Jordanian Legislation - Almomani, Hala Fayiz; Rajamanikam, Ramalinggam; Md. Said, Muhamad Helmi (Journal of Posthumanism, 2025)
This study presents a comprehensive analysis of community service punishment provisions in the Jordanian Penal Code compared to the practical provisions followed in the state of California, derived from the California Penal Code, system, and constitution. By employing a legal analysis approach alongside an extensive review of relevant literature and real-life case studies, we sought to gain deeper insights into the impact of community service penalties in Jordan compared to their impact in California. This, in turn, will positively contribute to improving the procedures followed in Jordanian law in the future by providing a legal reference that assists Jordanian legislators during future amendments to the Penal Code. This effort will encourage judges to widely apply these penalties, especially since they have proven effective in reality in reducing recidivism rates and improving the behavior of offenders who have served community service penalties. The study will also refer to the content of several interviews conducted with individuals responsible for drafting the legal provisions related to community service penalties in Jordan and the judges responsible for applying these laws in Jordanian courts, in order to provide a better realistic and practical perspective on the Jordanian experience in this regard.